Accurate annotation of accessible chromatin in mouse and human primordial germ cells. Issue 11 (November 2018) - Li, Jingyi; Shen, Shijun; Chen, Jiayu; Liu, Wenqiang; Li, Xiaocui; Zhu, Qianshu; Wang, Beiying; Chen, Xiaolong; Wu, Li; Wang, Mingzhu; Gu, Liang; Wang, Hong; et al.
Abstract Extensive and accurate chromatin remodeling is essential during primordial germ cell (PGC) development for the perpetuation of genetic information across generations. Here, we report that distalcis -regulatory elements (CREs) marked by DNase I-hypersensitive sites (DHSs) show temporally restricted activities during mouse and human PGC development. Using DHS maps as proxy, we accurately locate the genome-wide binding sites of pluripotency transcription factors in mouse PGCs. Unexpectedly, we found that mouse female meiotic recombination hotspots can be captured by DHSs, and for the first time, we identified 12, 211 recombination hotspots in mouse female PGCs. In contrast to that of meiotic female PGCs, the chromatin of mitotic-arrested male PGCs is permissive through nuclear transcription factor Y (NFY) binding in the distal regulatory regions. Furthermore, we examined the evolutionary pressure on PGC CREs, and comparative genomic analysis revealed that mouse and human PGC CREs are evolutionarily conserved and show strong conservation across the vertebrate tree outside the mammals. Therefore, our results reveal unique, temporally accessible chromatin configurations during mouse and human PGC development.